Cloning, characterisation and expression of the apolipoprotein A-I gene in the sea bream (Sparus aurata) - Llewellyn, Lynda (2014)
A full length cDNA clone representing apolipoprotein A-I was isolated from a sea bream (Sparus aurata) liver library. The clone encodes a 261 amino acid protein which shows highest amino acid identity (38%) with salmon apolipoprotein A-I. Northern blot analysis showed strong expression of a 1.4 kb transcript in liver with lower expression in intestine. Expression of apolipoprotein A-I in intestine was markedly reduced by treatment with triiodothyronine (T3). ß 1998 Elsevier Science B.V. All rights reserved.